Adénocarcinome villoglandulaire Du Col Utérin: A Propos D’un Cas Et Revue De La Littérature - Rokotondrainibe, Fenohery Nalisoa; Ranaivoson, Haingo Voahangy Rabetafika; Ramiandrasoa, Lalaoarifetra Andriamampihantona; Randrianjafisamindrakotroka, Nantenaina Soa; Irène, Raivoherivony Zo (International Journal For Research In Biology & Pharmacy, 2019)
We report the case of a 42-year-old woman with metrorrhagia. The physical examination revealed an exophytic, friable mass with endocervical development. It affirmed the diagnosis of villoglandular adenocarcinoma of the cervix.